The Business of Women: Gender, Family, and Entrepreneurship in British Columbia, 1901-1971 - Buddle, Melanie Anne (University of Victoria, 2003)
This study examines female self-employment in British Columbia from 1901 to 1971. Entrepreneurial women comprised a small proportion of the total female labour force but they exhibited differences from the rest of the labour force that deserve attention. The study relies on the Census of Canada to gain perspective on trends in female self-employment over a broad time period; qualitative sources are also utilized, including Business and Professional Women’s Club records, to illustrate how individual businesswomen reflected patterns of age, marital status, and family observed at a broad level. The role of gender in women’s decisions to run their own enterprises and in their choice of enterprise is also explored. While the research focus is British Columbia, this study is comparative: self-employed women in the province are compared to their counterparts in the rest of Canada, but also to self-employed men, and to other working women, in both regions. Regionally, women in British Columbia had higher rates of self-employment than women in the rest of the country between 1901 and 1971. Self-employed women in both British Columbia and Canada were, like wage-earning women, limited to a narrow range of occupational types, but they were more likely to work in male-dominated occupations. Self employed women were also older and more likely to be married, widowed or divorced than wage-earning women; in these aspects, they resembled self-employed men. But there were gender differences: whether women worked in female or male-dominated enterprises, they stressed their femininity. The need to take care of their families, particularly if they had lost a spouse through death or desertion, provided additional rationale for women’s presence in the business world. Family, marital status, age, gender and region all played a role in women’s decisions to enter into self-employment between 1901 and 1971.

The Search for Solidarity: The Industrial and Political Roots of the Cooperative Commonwealth Federation in British Columbia, 1913-1928 - Isitt, Benjamin (University of Victoria, 2003)
Born out of the industrial and political struggles of organized labour at the end of the First World War, the BC CCF was a product of organizational and ideological conflict in the 1910s and 1920s. This study explores the shift of BC socialism towards industrial action, which culminated in the One Big Union and the sympathetic strikes of 1919. It then examines the emergence of anti-Communism on the Left, shaped by the experience of political unity and disunity during the 1920s. These two factors fundamentally influenced the ideology and strategy adopted by the Cooperative Commonwealth Federation (CCF) in British Columbia. The ideological and tactical divisions of the 1930s were contested during the 1910s and 1920s. The collapse of the One Big Union, combined with deteriorating relations with the Communist Party, shifted BC socialists away from industrial militancy and toward parliamentary forms of struggle.

Searching for the Springs of Health: Women and Working Families in Winnipeg's 1918-1919 Influenza Epidemic - Jones, Esyllt Wynne (University of Manitoba, 2003)
In the winter of 1918-1919, a pandemic of influenza crossed the globe, killing as many as 50 million people. This dissertation is a local study of influenza in Winnipeg, Canada. It dissects the social responses to the disease from four different perspectives: that of the public health and medical authorities; middle class Anglo-Canadian women volunteers who provided nursing care and material relief to the city's poorer influenza victims; working class and immigrant families; and organized labour. The dissertation argues that the influenza epidemic, coming on the heels of the devastating Great War, and arriving in the midst of class, ethnic, and gender conflicts, played a role in deepening the social cleavages of Winnipeg society in the period, particularly those of class and ethnicity. Class and ethnic tension was not the inevitable outcome of the epidemic. Rather, it was the result of the social inequality of the disease's impact–working families represented a disproportionately high number of influenza's victims–and the failure of public authorities to mount a compassionate and cooperative community effort to fight the disease. The volunteerism of middle class Anglo-Canadian women, too, failed to build the bonds of community. Labour believed that the state response to influenza was a betrayal of principles of justice and public good. Workers' families bore the brunt of public closures and layoffs. A spirit of mutualism sustained families and neighbourhoods through the disease, and contributed to the mobilizing successes of the workers' movement in 1918-1919. The trauma of the epidemic suggested the fragility of the social order, and workers' capacity to build an alternative society. Their vision of social transformation included the creation of the "springs of health": a living wage, quality housing, and equal access to a democratic medical system. Many working families, nevertheless, found it difficult to recover from the loss of spouses and children. Their stories suggest that influenza had a long-term impact upon the evolution of post-war Canada that we are only just beginning to understand.

Divided We Stand: A Study of the Development of the Conflict Between the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America in Sudbury, Ontario (1942-1969) - Miller, Jason A. (McMaster University, 2003)
During the height of the Cold War, a new form of conflict among Canadian workers emerged along political lines. In some cases, the major source of conflict shifted from that of union versus management to left-wing union versus right-wing union. This thesis focuses on such an inter-union battle between the International Union of Mine, Mill and Smelter Workers and the United Steelworkers of America in Sudbury, Ontario from 1942 to 1969. ln this analysis, which attempts to incorporate the perspectives of the unions, the mine operators, and the Catholic Church and its affiliate organizations, it will be shown that despite the profound influence of the union executives, the media, the Church, and other prominent figures, the final decision regarding which union to join was ultimately made by the rank-and- file members at Inco and Falconbridge (with the miners at Inco choosing the Steelworkers as their bargaining agent while the miners at Falconbridge chose to remain with Mine-Mill).
https://macsphere.mcmaster.ca/bitstream/11375/12227/1/fulltext.pdf

Workers, Labour Unions and the Law: Canadian Labour Unions in the New World of Bilateral Freedom of Association - Sauve, David (Carleton University, 2003)
What are the consequences for the Canadian Labour movement in holding contradictory positions concerning freedom of association? The research into this question conceptualizes Canadian unions as partners with capital and the state in a legally constructed regime of labour relations and collective bargaining. Pertinent Supreme Court of Canada cases concerning labour unions and freedom of association demonstrate that labour unions are inconsistent in their claims concerning freedom of association. This study reveals that while labour unions claim freedom of association is unilateral, that is, workers do not have a right to dissociate, the courts have found that freedom of association is bilateral and workers have a constitutional right to not associate or associate with whom they choose. To date, the courts have also found that infringing on workers' freedom of association is justified under the 'Charter'. However, in the future, the courts may well find these infringements are not justified.

Bankers and Bomb Makers: Gender Ideology and Women's Paid Work in Banking and Munitions During the First World War in Canada - Street, Kori (University of Victoria, 2003)
During the First World War, some Canadian women found themselves in new and unfamiliar environments, doing jobs apparently unavailable to them before the war. Many of those women were successful in the new opportunities available to them. The focus of this study is twofold. First, it examines the scope and the nature of women's work in two industries, banking and munitions, during the war. This is an important step because we still know very little about women's experience of the war. Understanding how many women worked and in what capacity is essential to understanding the nuances of women's wartime experience. Women who worked in banking and munitions were not a homogeneous group. The composition of the wartime workforce is also analysed. The war's impact on wage rates for women is also examined. Second, the study focuses on the nature of the impact of wartime participation on gender ideology. In particular, the study seeks to determine if gender ideology was affected by women's expanded opportunities in masculine occupations during the war. Often, the historiography regarding women and war is characterised by a binary discourse that seeks to determine whether on not wars liberate women. Rather than engage in that debate, this study attempts to avoid it as much as possible. Women's experience of the war in these two industries was complex. The study explores how women could both challenge and reaffirm ideas about gender; how attitudes towards and about women could change and remain the same; and how employee and employers alike strove to undermine and maintain the sexual division of labour and labour processes that were threatened by the entrance of large numbers of women into jobs defined as men's work. Women's participation both challenged and reinforced traditional notions about gender. Essentially, despite being successful ‘bankers’ women remained unsuitable for a career in banking. Similarly, regardless of their participation in munitions factories, metal shops remained no place for women. Quantitative, oral interview and qualitative sources including contemporary newspapers and magazines, were used. In particular, a great deal of the evidence was derived from several databases constructed for this project.